Efficacy of 3 Different Steroid Treatments for Sudden Sensorineural Hearing Loss: A Prospective, Randomized Trial. Issue 1 (16th October 2012) - Lim, Hye Jin; Kim, Yun Tae; Choi, Seong Jun; Lee, Jong Bin; Park, Hun Yi; Park, Keehyun; Choung, Yun‐Hoon
Abstract : Objectives: We treated patients with idiopathic sudden sensorineural hearing loss (ISSNHL) with several protocols on an outpatient department (OPD) basis. The study compared the efficacy of 3 different steroid treatments for ISSNHL. Study Design: A prospective randomized controlled study. Setting: Tertiary referral center. Methods: A total of 60 patients diagnosed with ISSNHL were treated through OPD. They were randomly and equally divided into 3 groups based on therapy: oral steroid for 10 days (group I), intratympanic dexamethasone injection (ITDI) 4 times (group II), and both (group III). Pure‐tone average (PTA) was measured by taking 4 frequencies (0.5, 1, 2, and 3 kHz). Hearing change was evaluated by comparing pre‐ and posttreatment PTAs. Recovery rate was assessed by American Academy of Otolaryngology—Head and Neck Surgery (AAO‐HNS) Clinical Practice Guidelines. Results: The hearing gain was 12.8 ± 15.4 decibels (dB) in group I, 12.1 ± 14.6 dB in group II, and 21.9 ± 26.2 dB in group III. The recovery rate was 60% in groups I and III and 55% in group II. The overall recovery rate was 58.3% (35 of 60 patients). There was no significant difference in hearing gain and recovery rates for the 3 groups. Frequency‐specific hearing gain also did not differ significantly among groups. Conclusion: Three different treatment protocols (oral steroid, ITDI, or the combination) resulted in similar hearing recovery rates. Therefore, OPD‐based systemic and/or local steroid therapy can be recommended as an initial treatment in ISSNHL.